Determination of Cadmium (II) in Everlasting Flower Tea Samples by Flame Atomic Absorption Spectrometry (FAAS) Following Supramolecular Solvent Based Spray Assisted Microextraction - Yildirim, Vedat; Kartoglu, Bedrihan; Bodur, Suleyman; Atakol, Melike; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2026)
Helichrysum arenarium is used in traditional medicine due to several features. Nevertheless, the plant can accumulate cadmium (II) at elevated concentrations when cultivated in soils contaminated with heavy metals. For this reason, the determination of cadmium (II) in herbal beverages used in traditional medicine is a crucial topic to enhance human health. In this study, a method integrating supramolecular solvent based spray assisted liquid phase microextraction (SUPRAS-SA-LPME) with flame atomic absorption spectrometry (FAAS) is demonstrated to quantify cadmium (II). The synthesis of SUPRAS was carried out using tetrahydrofuran (THF) and decan-1-ol as reagents and 1,5-diphenyl carbazone (complexation agent) was dissolved in the synthesized SUPRAS to simultaneously perform the preconcentration and complexation steps. Under the optimized conditions, the developed method yielded mass-based detection/quantification limits (LOD/LOQ) of 2.17 mu g/kg/7.25 mu g/kg with a dynamic range from 7.67 mu g/kg to 102.73 mu g/kg. Spiked samples of everlasting flower tea were analyzed to assess the method's accuracy and applicability, obtaining recovery values in the range of 89.9%-145.3% based on a matrix-matching calibration strategy.
Keywords: Cadmium (II); everlasting flower tea; flame atomic absorption spectrometry (FAAS); liquid phase microextraction; supramolecular solvent based spray assisted liquid phase microextraction (SUPRAS-SA-LPME); LIQUID-LIQUID MICROEXTRACTION; ENVIRONMENTAL-SAMPLES; TRACE CADMIUM; EXTRACTION; PRECONCENTRATION; MERCURY; METALS; HEALTH; COPPER; FRUIT; Chemistry